Analisa Kondisi Sosial Ekonomi Petani Dengan Penerapan Good Agricultural Practices Padi Organik - Suswadi; Majasto; Sutarno; K Prasetyowati; Mahananto (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Organic farming is increasingly being applied to several agricultural commodities, one of which is rice as a rice-producing commodity and as a staple crop of most of Indonesia's population. In addition, the benefits of organic rice for the environment do not damage the environment, do not pollute the environment with synthetic chemicals and increase natural environmental productivity, as well as creating a balanced and sustainable ecosystem. The location of this research was conducted in the Pangudi Bogo farmer group in Dlingo Village, Mojosongo District, Boyolali District. The Pango Bogo group has received certification from the organic seloliman certification body (LESOS) and has consistently met the requirements of the SNI SOP GAP guidelines and the Internal Control System Document (ICS). This research uses descriptive analysis to illustrate the application of organic rice farming SOP-GAP. The influence of internal and external factors on the decision, the application of SOP-GAP and the handling of crop yields was tested using spermant rank correlation analysis. Based on the results of this study. SOP-GAP is a way to cultivate organic rice, which is to plant rice without using chemicals as a supplement or to repel pests and weeds. This SOP_GAP covers the types of maintenance, fertilization, irrigation and pest control activities. Maintenance is generally carried out by farmers by following organic farming instructions. Organic products and one of them is organic rice is a product that is currently of concern to consumers, especially consumers with upper middle economic level. This is because organic products are products that do not contain chemicals which have recently been the subject of discussion that chemicals in food ingredients cause various diseases. For those who have a sufficient economic level, then their attention is focused on health which is currently very expensive. That's why they turned to organic food products.